Storage stability and sensory evaluation of tocotrienol-rich-fraction-fortified mayonnaise - Teow, Shuh June; Choy, Hew Weng; Khor, Yih Phing; Tan, Tai Boon; Mat Yusoff, Masni; Gholivand, Somayeh; Tan, Chin Ping (Universiti Putra Malaysia, 2025)
Tocotrienol, a well-known antioxidant, was encapsulated within microcapsule for application in mayonnaise to determine the storage stability and sensory evaluation. Tocotrienol-rich fraction (TRF) nanoemulsion was first prepared by treated pea protein isolate-flaxseed gum complex, which was then spray dried into microcapsule using maltodextrin-starch sodium octenyl succinate. The present work aimed to determine the physico-chemical, oxidative, and sensory properties of TRF-fortified mayonnaises. Firstly, the control (C-Mayo) and TRF-fortified mayonnaise produced from microcapsule (M-mayo) and bulk oil (O-mayo) were stored at 4°C for four weeks. M-mayo was stable against storage due to low increments of lightness (1.19%), redness (7.50%), yellowness (9.11%), firmness (44.82%), consistency (63.22%), and viscosity (21.29%) as compared to C-mayo and O-mayo. In week 4, M-mayo showed a significantly lower peroxide value (2.66 mq/kg) compared to O-mayo (8.62 mq/kg). After storage, the degradation of tocopherol and tocotrienol isomers was lower in M-mayo (ranging from 11.86 to 30.76%) than in O-mayo (ranging from 22.23 to 34.15%). β-tocotrienol was the most unstable isomer in both types of mayonnaises during storage. In sensory evaluation, M-mayo obtained the highest rating for colour (7.60), while other sensory attributes (aroma, taste, creaminess, sourness, and overall acceptability) obtained similar ratings (ranging from 6.45 to 7.29) with other samples. Overall, the results showed that mayonnaise fortified with TRF microcapsule was able to reduce oxidation, and enhance their nutritional properties without affecting the sensory properties.